Academic performance and satisfaction with face-to-face, distance and blended teaching in entry-level physiotherapy programme: a retrospective comparative study - Dell'Isola, Andrea; Longhini, Jessica; Turolla, Andrea; Viceconti, Antonello; Gianola, Silvia; Beccucci, Giacomo; Patuzzo, Alberto; Rodeghiero, Lia; Battista, Simone; Geri, Tommaso; Palese, Alvisa; Rossettini, Giacomo (Acta Biomedica Atenei Parmensis, 2024)
Background and aim: The popularity of remote and blended teachings in physiotherapy higher education is increasing. Initial evidence suggests that these methods are as effective as face-to-face teaching for theoretical and practical skill learning in physiotherapy; however, further research is required. Methods: This was a retrospective comparative study. Three groups of physiotherapy students undertook the courses ’Biomechanics’ and ’Kinesiology’ through face-to-face, remote, and blended modalities, respectively. We compared the academic performance and satisfaction of three classes that underwent courses delivered face-to-face in 2019, remote in 2020, and blended in 2021. Each course included a basic observational skills section (25%). Oral examination assessed academic performance (mark range: 0-31). Student satisfaction was self-evaluated using a 5-point Likert scale (‘completely dissatisfied’ to ‘completely satisfied’). Differences in outcomes were explored using Fisher’s exact test and Kruskal Wallis test. Results: In the ‘Biomechanics’ course, the median mark (interquartile range) was 28 (27, 30) for the face-to-face group, 28.5 (27, 29) for the remote group and 29 (27, 30) for the blended group. In the ‘Kinesiology’ course, the median mark was 29 (27, 30) for the face-to-face, 28.0 (28, 30) for the remote and 29 (27, 30) for the blended. No statistically significant differences in academic performance were detected in either course. Satisfaction was good for both courses and teaching modalities; no statistically significant difference was detected. Conclusions: Students had similar satisfaction and academic performance, suggesting the potential efficiency of varying teaching methods in terms of learning and satisfaction.